Pengaruh Kualitas Pelayanan, Kualitas Sistem dan Kemudahan Akses dalam Penggunaan Aplikasi Barata Terhadap Kepuasan Masyarakat pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sragen - Ida Yuliana; Wagiyem (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of service quality, system quality, and ease of access on public satisfaction in using the BARATA application at the Department of Population and Civil Registration in Sragen Regency. The research method applied is quantitative with a survey approach, involving 92 respondents as the sample. Data analysis was conducted using multiple linear regression with SPSS version 25. The results indicate that all three independent variables significantly affect the dependent variable, both partially and simultaneously. System quality emerged as the most dominant factor in enhancing user satisfaction. These findings suggest that developing a reliable, easily accessible application system accompanied by high-quality service can increase public satisfaction. This research is expected to serve as a reference for the development of digital-based public service systems in government institutions.